Fuzje i przejęcia jako zewnętrzne strategie rozwoju przedsiębiorstwa - Zając, Czesław (Mergers and Acquisitions as External Development Strategies for Business, 2008)
Mergers and acquisitions are an example of the company’s development based upon an external growth. They are considered as a way of an integration of companies and as a phenomenon of the globalization of business. The paper presents the essence of mergers and acquisitions of companies. The study of publications done by the author helps to analyze the motives of them, especially those which have an international character, in the strategic dimension
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 20, s. 455-464